COMBINED ANTIHYPERTENSIVE THERAPY IN PATIENTS WITH ABDOMINAL OBESITY - O. D. Belyaeva; E. A. Bazhenova; O. O. Bolshakova; A. V. Berezina; O. A. Berkovich; E. I. Baranova (Российский кардиологический журнал)
.